Counseling and Watermelon Juice as Complementary Therapy for Pregnancy Hypertension in Aek Haruaya Village, Padang Lawas Utara - Riska Yanti; Melia Shintia Mutiara Pohan; Ayu Wulandari (PT Inovasi Pratama Internasional, 2025)
Hypertension in pregnancy remains a leading cause of maternal morbidity and mortality, particularly in rural areas with limited healthcare access. This community service program aimed to improve knowledge and reduce blood pressure among hypertensive pregnant women through counseling and watermelon juice intervention in Aek Haruaya Village, North Padang Lawas. Thirty pregnant women with gestational hypertension, chronic hypertension, or mild preeclampsia (20–34 weeks gestation) participated in a 14-day program consisting of interactive health education sessions and consumption of 300 ml fresh watermelon juice twice daily. Knowledge was measured using a 20-item questionnaire pre- and post-counseling, while blood pressure was monitored at baseline and day 14. Results showed a significant increase in knowledge scores from 52.3 ± 8.7 to 84.6 ± 6.2 (p < 0.001). Systolic blood pressure decreased from 148.7 ± 10.2 mmHg to 132.4 ± 8.9 mmHg (mean reduction 16.3 mmHg, p < 0.001), and diastolic blood pressure decreased from 95.3 ± 7.1 mmHg to 84.6 ± 6.4 mmHg (mean reduction 10.7 mmHg, p < 0.001). No serious adverse effects were reported, and adherence reached 93.3%. The combination of culturally tailored counseling and locally available watermelon juice effectively improved knowledge and significantly reduced blood pressure in hypertensive pregnant women. This community-based intervention offers a low-cost, safe, and sustainable complementary strategy for managing pregnancy hypertension in underserved rural settings.